pH and Temperature Dependent Gut Enzyme Niche in a Stomachless Herbivorous Freshwater Fish Amblypharyngodon mola (Hamilton, 1822) - Debnath, S.; Maiti, S. I.; Saikia, S. K. (Journal of Scientific Research, 2020)
The activities of digestive α-amylase (E. C. 3.2.1.1), total proteases, and bile salt-activated lipase (E. C. 3.1.1.-) along the digestive tract (lengthwise divided into five equal parts) of a stomachless freshwater fish (n = 10, weight = 4.354±0.316 g, standard length = 21.641±2.271 cm) were measured at different pH and temperature levels. Different optimum pH and temperature for the activity of α-amylase (8-9, 35°C), proteases (7-8, 45°C), and lipase (8, 45°C) were observed. The first two regions of the digestive tract showed comparatively higher activity of all enzymes. The hierarchical clustering technique revealed three different enzymatically active regions, more inclined to pH in the digestive tract of the studied fish. The present study also supports that the stomachless gut of A. mola has substantial resemblances to the intestinal part of the digestive tract of fish.